A Vacuolar Phytosiderophore Transporter Alters Iron and Zinc Accumulation in Polished Rice Grains . Issue 1 (22nd July 2019) - Che, Jing; Yokosho, Kengo; Yamaji, Naoki; Ma, Jian Feng
Abstract : Knockout of a vacuolar transporter for a phytosiderophore enhances iron and zinc accumulation in polished rice grains through increasing solubilization of these metals deposited in the node. Abstract: Essential metals, such as iron (Fe) and zinc (Zn), in grains are important sources for seed germination and nutritional requirements, but the molecular mechanisms underlying their loading into grains are poorly understood. Recently, nodes in rice ( Oryza sativa ) were reported to play an important role in the preferential distribution of mineral elements to the grains. In this study, we functionally characterized a rice gene highly expressed in nodes, OsVMT ( VACUOLAR MUGINEIC ACID TRANSPORTER ), belonging to a major facilitator superfamily. OsVMT is highly expressed in the parenchyma cell bridges of node I, where Fe and Zn are highly deposited. The expression of OsVMT was induced by Fe deficiency in the roots but not in the shoot basal region and uppermost node. OsVMT localized to the tonoplast and showed efflux transport activity for 2′-deoxymugineic acid (DMA). At the vegetative stage, knockout of OsVMT resulted in decreased DMA but increased ferric Fe in the root cell sap. As a result, the concentration of DMA in the xylem sap increased but that of ferric Fe decreased in the xylem sap in the mutants. In the polished rice grain, the mutants accumulated 1.8- to 2.1-fold, 1.5- to 1.6-fold, and 1.4- to 1.5-fold higher Fe, Zn, and DMA, respectively, than the wild type. Taken together, our results indicate that OsVMT is involved in sequestering DMA into the vacuoles and that knockout of this gene enhances the accumulation of Fe and Zn in polished rice grains through DMA-increased solubilization of Fe and Zn deposited in the node.